The Influence of Social Media on Adolescent Social Behavior: A Case Study of TikTok Users in Bandung City - Muslimin, Muslimin (Eastasouth Institute, 2025)
This study aims to analyze the influence of TikTok social media on the social behavior of adolescents in Bandung City. Using a quantitative approach, data were collected from 200 adolescent TikTok users through questionnaires, then analyzed using simple linear regression. The results showed that the intensity of TikTok use had a significant effect on adolescent social behavior, with a positive correlation between the two variables. Intensive use of TikTok affects the way adolescents interact, imitate trends, and adopt new social norms, both in online and offline environments. In addition to providing a positive influence on aspects of creativity and social engagement, TikTok also has the potential to trigger antisocial behavior and a tendency to follow risky behavior. The implications of this study emphasize the importance of digital literacy, the role of parents, and policies that support healthy social media use for adolescents.